305 ENDOSCOPIC PYLORIC INJECTION OF BOTULINUM TOXIN FOR THE TREATMENT OF POSTVAGOTOMY GASTROPARESIS. Issue 1 (1st January 2007) - Reddymasu, S. C.; Singh, S.; Foran, P.; Sankula, R.; McCallum, R. W.
Abstract : Background: Gastroparesis is a common clinical condition characterized by nausea, vomiting, abdominal pain, postprandial fullness, loss of appetite, and, in severe cases, malnutrition. It is more prevalent in women, and common etiologies include diabetes, postsurgical usually secondary to a vagotomy and/or gastric resections, and idiopathic. Therapy includes prokinetic agents such as metoclopramide, domperidone, erythromycin, and nutritional support. Recently, botulinum toxin injected into the pylorus is being used to treat refractory gastroparesis, which is idiopathic or secondary to diabetes. Little is known about its efficacy in postsurgical gastroparesis due to vagal nerve and where in the past a surgical pyloroplasty would have been considered. Aims of the Study: To evaluate the efficacy of endoscopic injection of botulinum toxin injection into the pylorus of the stomach in patients with postsurgical gastroparesis. Methods: This open-labeled trial identified and recruited 11 patients who developed symptomatic gastroparesis after a surgical procedure (10 fundoplication, 1 exploratory laparoscopy). Gastroparesis was defined as an abnormal solid-phase gastric emptying test using the standardized 4-hour radionuclide egg beater meal method. Eight patients had vagal nerve injury documented by sham meal testing. Subjects were being followed in the gastrointestinal motility clinic and completed at least the sixth month follow-up visit after their pylorus was injected with botulinum toxin injection in a four-quadrant manner. Patients either received 100 ( n = 2) or 200 ( n = 9) units of botulinum toxin. Questionnaires recorded symptom severity beginning at baseline prior to the injection and at monthly intervals for the next 6 months. Nausea, vomiting, abdominal pain, early satiety, loss of appetite, and weight loss were scored on a scale of 0 to 5 for severity. All but one patient completed the questionnaire. Results: Seven females and three males (age range 31-84 years) finished the sixth month follow-up visit. The mean symptom score prior to therapy was 18 ± 5.8 (1 SD) and showed a consistent and significant ( p < .005 using the paired t -test) decline over the 6-month period to 10 ± 7.7 (1 SD). Results are shown in Figure 1 . A marked decline in symptom severity was noted in the initial 2 to 3 months after the pyloric injection. No complications were recorded. Conclusions: Endoscopic injection of botulinum toxin in the pylorus appears to be a safe and effective addition to the therapeutic armamentarium for refractory postvagotomy gastroparesis. Randomized trials with botulinum toxin injections seem warranted in this subset of gastroparesis.